2013
DOI: 10.1155/2013/363076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofIn VitroAnti-Inflammatory Activities and Protective Effect of Fermented Preparations of Rhizoma Atractylodis Macrocephalae on Intestinal Barrier Function against Lipopolysaccharide Insult

Abstract: Lipopolysaccharide (LPS), a potent inducer of systemic inflammatory responses, is known to cause impairment of intestinal barrier function. Here, we evaluated the in vitro protective effect of an unfermented formulation of Rhizoma Atractylodis Macrocephalae (RAM), a traditional Chinese herbal medicine widely used in the treatment of many digestive and gastrointestinal disorders, and two fermented preparations of RAM, designated as FRAM-1 (prepared in Luria-Bertani broth) and FRAM-2 (prepared in glucose), on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…In previous research, the extracts of A. macrocephala possessed notable anti-inflammatory and protective effect on intestinal barrier function against insult of LPS (Bose & Kim, 2013). However, few related monomers were reported.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous research, the extracts of A. macrocephala possessed notable anti-inflammatory and protective effect on intestinal barrier function against insult of LPS (Bose & Kim, 2013). However, few related monomers were reported.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, we have found that atractylenolide I (AT-I) showed a good neutralization effect on LPS and inhibitory effects against TNF-a and IL-6. AT-I is one of the major active components of Atractylodes macrocephala Koidz (Compositae), which is a very important TCM used for treating digestive disorders and inflammatory diseases (Bose & Kim, 2013;Dong et al, 2007;Peng et al, 2011). Previous investigations have reported that AT-I had wide spectrum pharmacological activities in A. macrocephala, including anti-inflammation, antitumor, and antioxidant properties (Endo & Taguchi, 1979;Kang et al, 2011;Rittirsch et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ban-xia-xie-xin-tang can mitigate nausea and vomiting caused by systemic cancer therapy 48,49. The other single herbs such as sha-ren ( Amomi fructus ) and bai-zhu ( Atractylodis macrocephalae rhizoma ) can modulate gastrointestinal symptoms 50,51…”
Section: Discussionmentioning
confidence: 99%
“…Biological system on exposure to different physiochemical and pathological states lead to the generation of numerous free radical species (reactive nitrogen species and ROS) [13] resulting in a condition called oxidative stress, where free radicals are generated beyond the body's ability to regulate their production. Oxidative stress if left uncontrolled lead to chronic inflammatory conditions such as…”
Section: Discussionmentioning
confidence: 99%